2001
DOI: 10.1107/s1600536801015240
|View full text |Cite
|
Sign up to set email alerts
|

L-Phenylalaninium maleate

Abstract: Key indicatorsSingle-crystal X-ray study T = 293 K Mean '(C±C) = 0.003 A Ê R factor = 0.028 wR factor = 0.078 Data-to-parameter ratio = 7.2 For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 5 publications
6
19
0
Order By: Relevance
“…It has a crystalline structure containing various types of hydrogen bonds besides the intramolecular one of interest, and molecules form crystal networks stabilized by shorter O-HÁ Á ÁO and longer N-HÁ Á ÁO hydrogen bonds between the ions. The only reported prior attempt to determine the structure of l-phenylalaninium hydrogen maleate was based on low-resolution X-ray diffraction data and resulted in an asymmetric hydrogen position in the intramolecular hydrogen bond with the O-H bond lengths 1.13/1.28 Å (Alagar et al, 2001). In a different X-ray study, reported for the racemic dl-phenylalaninium hydrogen maleate, all the hydrogen atoms were positioned geometrically, which led to an even more asymmetric hydrogen bond (Rajagopal et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It has a crystalline structure containing various types of hydrogen bonds besides the intramolecular one of interest, and molecules form crystal networks stabilized by shorter O-HÁ Á ÁO and longer N-HÁ Á ÁO hydrogen bonds between the ions. The only reported prior attempt to determine the structure of l-phenylalaninium hydrogen maleate was based on low-resolution X-ray diffraction data and resulted in an asymmetric hydrogen position in the intramolecular hydrogen bond with the O-H bond lengths 1.13/1.28 Å (Alagar et al, 2001). In a different X-ray study, reported for the racemic dl-phenylalaninium hydrogen maleate, all the hydrogen atoms were positioned geometrically, which led to an even more asymmetric hydrogen bond (Rajagopal et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…3 in Natarajan et al (2008) a C 3 3 (17) motif can be seen. References: (1) Rajagopal, Krishnakumar, Mostad & Natarajan (2001); (2) Alagar et al (2001a); (3) Alagar et al (2001b); (4) Alagar et al (2003); (5) Alagar et al (2001c); (6) and (7) Arkhipov et al (2013); (8) Alagar et al (2002); (9) Ilczyszyn et al (2003); (10) and (17) Fleck et al (2013); (11) Rajagopal et al (2004); (12) ; (13) and (18) Pratap et al (2000); (14) crystallizes from solution, but another salt in the presumable 1:1 ratio, which we have defined as (III) 0 . The formation of (III) 0 was complete, with no peaks of remaining maleic acid or of l-norvaline present in the diffraction patterns.…”
mentioning
confidence: 99%
“…In 2ATHM, an intramolecular hydrogen bond between atoms O1 and O4 of the semimaleate anion is asymmetric and generates an S(7) motif (Bernstein et al, 1995), as observed in 8-hydroxyquinolinium hydrogen maleate (Franklin & Balasubramanian, 2009). This intramolecular hydrogen bond with an S(7) motif is a common occurrence in several salts of maleate (Alagar et al, 2001(Alagar et al, , 2002Rajagopal et al, 2001Rajagopal et al, , 2002. The corresponding intramolecular hydrogen bond with an S(5) motif is found in the semifumarate anion of 8-hydroxyquinolinium hydrogen fumarate (Franklin & Balasubramanian, 2009) but is not observed here in the semifumarate anions of 2ATHF.…”
Section: Figurementioning
confidence: 90%
“…Crystal structures and hydrogen-bonding patterns of derivatives of 2-amino-1,3-thiazole have already been reported (Lynch, 2002;Lynch & McClenaghan, 2004, 2005Glidewell et al, 2004). Maleic acid, the Z isomer of butenedioic acid, is a simple building block in two-and threedimensional supramolecular architectures (Bowes et al, 2003;Jin et al, 2003), and many crystal structures of 1:1 organic salts of maleic acid with organoamines have been reported to explain their aggregation patterns and hydrogen-bonding interactions (Alagar et al, 2001;Rajagopal et al, 2001;Lah & Leban, 2003). In all such structures, the maleic acid exists in either a monoionized state or its fully deprotonated form.…”
Section: Commentmentioning
confidence: 98%